Theoretical study of analytical wake models for yawed wind turbines (2024)
The present study will explore some of the most relevant engineering wake models for yawed wind turbines developed to date. Compared to wind tunnel tests and numerical simulations, analytical wake models have greater applications in real wind farm control and optimization because of their simplicity and high efficiency. These engineering models were implemented in PyWake [9], an open source and Python-based wind farm simulation tool developed at DTU capable of computing flow fields, power production of individual turbines, as well as the Annual Energy Production (AEP) of a wind farm. This software can quantify the interaction between turbines and calculate wake propagation inside a wind farm with excellent efficiency. In addition, high-fidelity SOWFA simulations, performed by the CL-Windcon project, were used to validate the models mentioned above and their implementation.